PENANGANAN TERHADAP TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA PADA TAHAP PENYIDIKAN DI WILAYAH HUKUM KEPOLISIAN RESOR BOYOLALI - SUNYOTO, EDI (Dinamika Hukum, 2015)
The purpose of this study is to examine and explain the handling of the criminal offense of abuse of narcotics at the investigation stage in the jurisdiction. Examines and explains the obstacles in the handling of criminal acts abuse of drugs in the investigation stage in the jurisdiction of Police Boyolali. This research method using normative juridical type of research, which is done by examining secondary data sources, which consist of primary legal materials, secondary law, and tertiary legal materials. The nature of descriptive research, the research is intended to provide data as accurately as possible about the people, circumstances or other symptoms. Treatment at this stage of the investigation of the criminal offense of abuse of narcotics in the Police Law Boyolali namely: receiving reports from the public about the alleged criminal act then Police Narcotics abuse Boyolali make police report on the report after it is created Warrant and Warrant Investigation Task then Member Police Boyolali to act first on the scene found the suspect and evidence, then perform forceful measures against the suspect in the form of arrest, search and seizure of evidence and urine tests conducted against the suspect in the Forensic Laboratory, the next suspect Examination (Investigator make Interrogation ), during arrests, investigators complement case file and send the case file to the District Attorney Boyolali and otherwise have a complete dossier (P-21), after it is done delivery phase suspect and any evidence to the State Attorney Boyolali. Barriers in the handling of criminal acts of abuse of narcotics at the investigation stage in the jurisdiction of Police Boyolali, is the lack of cooperation between police (Investigator) with a society that does not want to report the occurrence of the crime of drug abuse on the grounds do not want to be a witness because not bother other people's business. The criminal misuse of narcotic remove traces of time will do a search, giving a convoluted explanation. Limited facilities and infrastructure including vehicles owned by the Police Boyolali to conduct patrols in each region who are considered vulnerable. Limited human resources (police) is the lack of professionals in conducting the investigation. Keywords: Management, Crime, Abuse, Narcotics